2008
DOI: 10.1371/journal.pmed.0050100
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Load and Viral Sequence Diversification Determine the Functional Profile of HIV-1–Specific CD8+ T Cells

Abstract: BackgroundVirus-specific CD8+ T lymphocytes play a key role in the initial reduction of peak viremia during acute viral infections, but display signs of increasing dysfunction and exhaustion under conditions of chronic antigen persistence. It has been suggested that virus-specific CD8+ T cells with a “polyfunctional” profile, defined by the capacity to secrete multiple cytokines or chemokines, are most competent in controlling viral replication in chronic HIV-1 infection. We used HIV-1 infection as a model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
218
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(253 citation statements)
references
References 44 publications
35
218
0
Order By: Relevance
“…As a correlation of the degree of CD8 + T-cell exhaustion with the viral load was observed in M. tuberculosis [27] and HIV [24,26] infected humans, our findings likely have a strong relevance for treatment of chronically infected patients. It is currently widely discussed to treat chronically infected patients with regimes aimed at boosting the antiviral CD8 + T-cell response, for example, with antibodies blocking the interaction of PD-1 and PD-L1 [50] (in combination with antibodies directed against other inhibitory receptors [51,52]).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…As a correlation of the degree of CD8 + T-cell exhaustion with the viral load was observed in M. tuberculosis [27] and HIV [24,26] infected humans, our findings likely have a strong relevance for treatment of chronically infected patients. It is currently widely discussed to treat chronically infected patients with regimes aimed at boosting the antiviral CD8 + T-cell response, for example, with antibodies blocking the interaction of PD-1 and PD-L1 [50] (in combination with antibodies directed against other inhibitory receptors [51,52]).…”
Section: Discussionsupporting
confidence: 60%
“…Finally, it is conceivable that extensive killing of antigen-presenting DCs might be involved in the observed pathology in chronically infected DC-MHCI mice, potentially leading to severe immunosuppression and inability of chronically infected mice to cope with other viral or bacterial infections. However, this hypothesis is rather unlikely as the number of DCs was not severely compromised in chronically infected DC-MHCI mice and since development of pathology was very acute which is unlikely to be caused by heterologous infections in the setting of a clean specific pathogen free facility.As a correlation of the degree of CD8 + T-cell exhaustion with the viral load was observed in M. tuberculosis [27] and HIV [24,26] infected humans, our findings likely have a strong relevance for treatment of chronically infected patients. It is currently widely discussed to treat chronically infected patients with regimes aimed at boosting the antiviral CD8 + T-cell response, for example, with antibodies blocking the interaction of PD-1 and PD-L1 [50] …”
supporting
confidence: 60%
See 2 more Smart Citations
“…There has been considerable evidence that the initial viral load inversely correlates with the functionality of Ag-specific CD8 + T cells (10,54,55). Recently, a combined in situ tetramer staining and in situ hybridization approach showed that relative rates of increase in Agspecific effector CD8 + T cells and virally infected targets during the early stage predict the outcome of viral infection (56).…”
Section: Discussionmentioning
confidence: 99%